Demografía zootécnica aplicada a los Camélidos Sudamericanos Domésticos - Hick, Michel Victor Hubert; Prieto, Alejandro; Castillo, Maria Flavia; Flores Gutiérrez, Alfonso; Mamani Cato, Rubén Herberht; Frank, Eduardo (SUPPRAD, 2021)
81 páginas